DcaP porin and its epitope-based subunit promise effective vaccines against Acinetobacter baumannii; in-silico and in-vivo approaches. (January 2022) - Raoufi, Zeinab; Abdollahi, Sajad; Armand, Raham
Abstract: A. baumannii is a multi-drug resistant pathogen with a relatively high mortality rate. To date, no vaccine has been approved against this bacterium. DcaP is a high abundance porin during infection that its structure has been recently determined, but no information about its immunogenic properties has been reported yet. So, in this study DcaP properties were analyzed and its vaccine potential was evaluated. The results showed this porin is an extremely conserved antigen with no allergenicity and toxicity that bears no resemblance to human proteins. Six potential immunogen areas in the DcaP sequence were detected based on in-silico B and T-cell epitope mapping and other approaches. A multiple-epitope potential vaccine was designed based on the predicted linear epitopes and amplified by overlap extension PCR technique. In-vivo results indicated that active and passive immunization of mice with the DcaP protein or its designed subunit vaccine raises the antibody titers and decreases the mortality rate of the immunized mice infected with A. baumannii . Based on the results, DcaP and its indicated immunogen regions can be considered as a peptide or subunit vaccine. The immunogen regions could also be applied in multivalent subunit vaccine candidates against A. baumannii and other bacteria. Highlights: DcaP is an extremely conserved antigen with no similarity to human proteins. Six immunogen regions were reported based on B and T-cell epitope mapping. Mice immunized with DcaP or its immunogen regions showed a lower mortality rate. DcaP and its immunogen regions can serve as peptide or sub-unit vaccines.